ENZYME PROFILE OF PERIPHERAL BLOOD LYMPHOCYTES IN PATIENTS WITH THE RENAL CELL CARCINOMA BEFORE AND AFTER SURGICAL TREATMENT - L. M. Kurtasova (SPb RAACI, 2018)
The aim of the study was to investigate activities of NAD- and NADP-dependent dehydrogenases in peripheral blood lymphocytes of the patients with renal cell carcinoma (RCC) at the terms before surgery and 14 and 30 days after surgical treatment. The patients at the age of 45-55 years with locally advanced RCC were examined before surgical treatment, 14 and 30 days after surgery. The control group consisted of healthy donors of the same age range. Activity of NAD- and NADP-dependent dehydrogenases was determined by bioluminescence method using bienzyme complex isolated from luminescent bacteria. The enzyme profile changes of peripheral blood lymphocytes in the patients with RCC in pre- and postoperative period have been revealed. The lymphocyte metabolism in patients with RCC at the pre-operative period was characterized by decreased activity of pentose phosphate cycle, and glutathione-dependent antioxidant system. The changes in activity of these processes may lead to decreased levels of macromolecular synthetic reactions in the lymphocytes and activation of peroxide reactions. We have registered a decreased activity of lactate dehydrogenase anaerobic reaction which characterizes inhibition of the terminal anaerobic glycolysis reactions. The levels of metabolic reactions in blood lymphocytes from the RCC patients in preoperative period determining the intensity of aerobic respiration corresponded to control values, along with an increased intensity of the NAD-dependent substrates outflow from the tricarboxylic acid cycle to the amino acid exchange reaction. In the postoperative period in patients with RCC in blood lymphocytes the activity of the terminal reactions of the anaerobic glycolysis hold on, the aerobic lactate dehydrogenase reaction moderately activated. During the entire postoperative period, an increased outflow of NAD-dependent substrates from the tricarboxylic acid cycle to the amino acid exchange reaction is registered in blood lymphocytes of RCC patients. Nevertheless, there is a significant increase in the intensity of the Krebs cycle terminal reactions, which determines an increase in aerobic respiration activity being energetically more beneficial to the cells. At the same time, «impoverishment» of the pentose phosphate cycle metabolites in the lymphocytes of the patients with RCC, due to similar redistribution of the substrate flows, leads to decreased plastic processes in cells. Even 30 days after surgical treatment, a decrease remains in glutathione-dependent antioxidant protection of the cells. Therefore, the patients with RCC need correction of metabolic processes in the immune cells during postoperative period. This fact should be taken into account by developing rehabilitation programs in this category of the patients.